Complex hybridization patterns in European pond turtles (Emys orbicularis) in the Pyrenean Region - Pöschel, Julia; Wink, Michael (Scientific reports, 2018)
Hybrid zones are natural laboratories allowing insights in genetic processes like lineage diversification, speciation and introgression. Using large sampling, 15 microsatellite loci and a mitochondrial marker, we examined the Pyrenean contact zone of three pond turtle taxa (Emys orbicularis orbicularis, E. o. galloitalica, E. o. occidentalis).
Gesehen am 23.04.2020